Perancangan Rangkaian Smart Trash Bin - M Reja Hilmansyah L; Aly Mulkan Arifuddin; Muhammad Nazeem Al Ghozali; Devka Nanda Juniandi (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2024)
To enhance awareness of environmental cleanliness and prevent the spread of diseases or viruses, it is sometimes necessary to employ unique methods to attract people's interest, thereby encouraging them to dispose of waste properly. Traditional trash bins generally require manual operation to open and close, which can be inconvenient for users and increase interaction between people and the trash bin. Moreover, manual trash bins often struggle to manage waste when they are full. This research, conducted by Institut Teknologi Nasional, offers a solution by designing a smart trash bin based on Arduino Uno, utilizing the HC-SR04 or ultrasonic sensors, a servo motor, and a buzzer or speaker. In this smart trash bin, the HC-SR04 ultrasonic sensor is used to detect distance, while the servo motor functions to open and close the lid. The buzzer or speaker provides notifications when the lid is about to open or when the trash bin is full.